Pengaruh Kecemasan dan Self-Regulated Learning terhadap Prestasi Belajar Matematika Menggunakan Sem-Amos - Intan Pramida Kusuma; Wiwit Wahyu Rosmawati; Wanda Nugroho Yanuarto (Advances In Education Journal, 2026)
This study uses the Structural Equation Modeling (SEM) method with the assistance of IBM SPSS AMOS to identify and analyze the influence of anxiety and independent learning on students' mathematics learning achievement. The quantitative approach is used because the data collected is in the form of numbers and is statistically analyzed to evaluate the relationships between variables. The background of this research lies in the fact that students still often experience poor math learning achievement. Mathematics is considered a difficult subject by many students, which makes them anxious and scared when studying and working on problems. This condition is called math anxiety. Students who experience high levels of anxiety can have difficulty concentrating, lose confidence, and give up when solving math problems. As a result, students' math skills decline. In addition to the anxiety factor, the ability to self-regulate learning is also one of the important factors that affect mathematics learning achievement. Self-regulated learning is the ability of students to manage and control their learning process independently, such as managing learning time, determining learning goals, choosing the right learning strategy, and evaluating the learning outcomes that have been achieved. Students who have good self-regulation skills tend to be more disciplined, active, and responsible in the learning process so that they are able to obtain better learning outcomes.  The research data was obtained through the distribution of questionnaires to students to measure the level of anxiety and self-regulated learning, as well as documentation of students' mathematical scores as data on learning achievement. The data analysis technique was carried out using SEM-AMOS through several stages, namely validity test, reliability test, Confirmatory Factor Analysis (CFA), structural model testing, and goodness of fit test  to determine the feasibility of the research model. The results of the study showed that anxiety had a negative and significant effect on mathematics learning achievement. This means that the higher the level of anxiety of students, the higher the achievement of learning mathematics tends to decrease. On the other hand, self-regulated learning has a positive and significant effect on mathematics learning achievement, which means that the better the student's ability to manage the learning process, the higher the mathematics learning achievement obtained. In addition, the results of the goodness of fit test  show that the research model has met the model feasibility criteria so that the SEM model used is declared feasible and can be used to explain the relationship between variables in the study. Based on the results of the study, it can be concluded that anxiety and self-regulated learning are important factors that affect students' mathematics learning achievement. Therefore, efforts are needed from teachers and schools to create a comfortable learning atmosphere, reduce student anxiety, and improve students' self-regulation skills so that mathematics learning achievement can increase.